PRESIDENCY IN UKRAINE: PROBLEMS OF INSTITUTIONAL FORMATION, DEVELOPMENT AND FUNCTIONING - Москалюк, М. Ф. (PRECARPATHIAN BULLETIN OF THE SHEVCHENKO SCIENTIFIC SOCIETY Idea, 2019)
This paper examines the institute of the presidency in Ukraine and problems of its institutional formation, development and functioning. Based on the quantitative and especially the qualitative indicators was carried out the politological analysis of the presidency of Ukraine in the context of the evolutionary stages of its formation. As well an index assessment of the presidential powers was conducted. The author took into account the theoretical achievements of such western researchers as M. Shugart, J. Carey, J. McGregor, T. Fry, A. Siaroffa, A. Krouvel, C. Arminheon, R. Carei and domestic scientists A. Kudryachenko, Yu Surganova, M. Zelinsky, A. Romaniuk.. The influence of the form of republican government on the evolution of the status and functional characteristics of head of state, the role and place of the institution of presidency in the political systems of Ukraine was found out. The positive and problematic aspects of functioning of the national presidency was singled out.